[Afisz. Incipit] Tydzień Polskiego Czerwonego Krzyża w Kartuzach 16.6.1948-22.6.1948 ... (Kartuzy : [wydawca nieznany], 1948)
Afisz z programem obchodu 20.06.1948 r.
Keywords: Polski Czerwony Krzyż -- 1945-1970 -- druki ulotne; Kartuzy (Polska) -- 1945-1970 -- druki ulotne; Afisze -- 1945-1990.